Rafting‐Enabled Recovery Avoids Recrystallization in 3D‐Printing‐Repaired Single‐Crystal Superalloys. Issue 12 (20th February 2020) - Chen, Kai; Huang, Runqiu; Li, Yao; Lin, Sicong; Zhu, Wenxin; Tamura, Nobumichi; Li, Ju; Shan, Zhi‐Wei; Ma, Evan
Abstract: The repair of damaged Ni‐based superalloy single‐crystal turbine blades has been a long‐standing challenge. Additive manufacturing by an electron beam is promising to this end, but there is a formidable obstacle: either the residual stress and γ/γ ′ microstructure in the single‐crystalline fusion zone after e‐beam melting are unacceptable (e.g., prone to cracking), or, after solutionizing heat treatment, recrystallization occurs, bringing forth new grains that degrade the high‐temperature creep properties. Here, a post‐3D printing recovery protocol is designed that eliminates the driving force for recrystallization, namely, the stored energy associated with the high retained dislocation density, prior to standard solution treatment and aging. The post‐electron‐beam‐melting, pre‐solutionizing recovery via sub‐solvus annealing is rendered possible by the rafting (i.e., directional coarsening) of γ ′ particles that facilitates dislocation rearrangement and annihilation. The rafted microstructure is removed in subsequent solution treatment, leaving behind a damage‐free and residual‐stress‐free single crystal with uniform γ ′ precipitates indistinguishable from the rest of the turbine blade. This discovery offers a practical means to keep 3D‐printed single crystals from cracking due to unrelieved residual stress, or stress‐relieved but recrystallizing into a polycrystalline microstructure, paving the way for additive manufacturing to repair, restore, and reshape any superalloy single‐crystal product. Abstract : A post‐3D‐printing recovery protocol is designed to eliminate the driving force for recrystallization prior to standard solution treatment and aging. After heat treatment, a damage‐free single crystal, with uniform γ ′ precipitates indistinguishable from the rest of the turbine blade, is generated. This discovery paves the way for additive manufacturing to repair, restore, and reshape any superalloy single‐crystal product.